2011
DOI: 10.1074/jbc.m110.213975
|View full text |Cite
|
Sign up to set email alerts
|

HoxA10 Influences Protein Ubiquitination by Activating Transcription of ARIH2, the Gene Encoding Triad1

Abstract: HoxA10 is a homeodomain transcription factor that is maximally expressed in myeloid progenitor cells. An increase in HoxA10 expression correlates with poor prognosis in human acute myeloid leukemia (AML). Consistent with this scenario, HoxA10 overexpression in murine bone marrow induces a myeloproliferative neoplasm that advances AML over time. Despite the importance of HoxA10 for leukemogenesis, few genuine HoxA10 target genes have been identified. The current study identified ARIH2, the gene encoding Triad1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 35 publications
(65 reference statements)
3
57
0
Order By: Relevance
“…This result is consistent with the multiple HoxA10-binding sites found in other target genes, including CYBB, NCF2, DUSP4, and TGF␤-2 (19,21,22,(35)(36)(37). We found that HoxA10-binding affinity for the two FGF2 cis elements is approximately equivalent.…”
Section: Discussionsupporting
confidence: 79%
“…This result is consistent with the multiple HoxA10-binding sites found in other target genes, including CYBB, NCF2, DUSP4, and TGF␤-2 (19,21,22,(35)(36)(37). We found that HoxA10-binding affinity for the two FGF2 cis elements is approximately equivalent.…”
Section: Discussionsupporting
confidence: 79%
“…Oligonucleotides probes were prepared, and DNA binding was analyzed by electrophoretic mobility shift assay (EMSA) and DNA affinity purification techniques as described (18,(21)(22)(23)(24)(25)(26). For EMSA, antibody to HoxA9 or HoxA10 (or irrelevant control antibody) was included in binding assays.…”
Section: Methodsmentioning
confidence: 99%
“…We used chromatin immunoprecipitation-based screening techniques to identify HoxA10 target genes that might be relevant to leukemogenesis (21)(22)(23)(24)(25)(26). In these studies we identified the gene encoding fibroblast growth factor 2 (Fgf2, or basic Fgf) as a HoxA10 target gene (26).…”
mentioning
confidence: 99%
“…Expression of Triad1 is known to increase during granulopoiesis and impair proliferation of myeloid progenitor cells, but substrates for Triad1 in hematopoietic cells are not defined (17-21). In epithelial cells, Triad1-dependent ubiquitination results in lysosomal degradation versus re-cycling (and sustained signaling) of the receptors for epidermal growth factor and growth hormone (22).…”
Section: Introductionmentioning
confidence: 99%
“…We previously identified tandem cis elements in the ARIH2 promoter that are activated by the homeodomain transcription factor, HoxA10 (21). Unlike ARIH2 −/− mice, HOXA10 −/− mice are viable; unlike mice transplanted with ARIH2 −/− bone marrow, HOXA10 −/− mice do not exhibit steady state immune activation (23).…”
Section: Introductionmentioning
confidence: 99%